2015
DOI: 10.3390/ma8115401
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Deformation of Twin-Roll Cast Al-Mn-Based Alloys after Equal Channel Angular Pressing

Abstract: Twin roll cast Al-Mn- and Al-Mn-Zr-based alloys were subjected to four passes of equal channel angular pressing. The resulting grain size of 400 nm contributes to a significant strengthening at room temperature. This microstructure is not fully stable at elevated temperatures and recrystallization and vast grain growth occur at temperatures between 350 and 450 °C. The onset of these microstructure changes depends on chemical and phase composition. Better stability is observed in the Al-Mn-Zr-based alloy. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This is the case of the Al3003 alloy used in our research. Experiments performed on the 3003 aluminium alloy processed by ECAP [25] revealed that the sample after four ECAP passes contained a mixture of elongated grains containing numerous LAGBs and small equiaxed grains with the average size close to 500 nm. The ratio of HAGBs was close to 60%.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of the Al3003 alloy used in our research. Experiments performed on the 3003 aluminium alloy processed by ECAP [25] revealed that the sample after four ECAP passes contained a mixture of elongated grains containing numerous LAGBs and small equiaxed grains with the average size close to 500 nm. The ratio of HAGBs was close to 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their grain size sensitivity, the superplastic properties can be significantly improved by optimization of thermomechanical treatments [30,31] (including severe plastic deformation [32][33][34]) and chemical composition modification. Both methods focus on a grain refinement effect.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of studies have been done to investigate the ECAP processes of pure aluminum and high purity aluminum in both experiments and simulations, amongst which some factors such as extrusion route, extrusion passes, and die angles were studied more frequently [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. For general materials, the initial condition of the material is usually neglected due to less obvious particularity.…”
Section: Introductionmentioning
confidence: 99%